Expanding Insights on the Diversity Climate–Performance Link: The Role of Workgroup Discrimination and Group Size - Boehm, Stephan A.; Dwertmann, David J. G.; Kunze, Florian; Michaelis, Björn; Parks, Kizzy M.; McDonald, Daniel P. (Human Resource Management, 2014)
The present study extends knowledge of the performance consequences of workgroup diversity climate. Building upon Kopelman, Brief, and Guzzo's () climate model of productivity, we introduce workgroup discrimination as a behavioral mediator that explains the positive effects of diversity climate on workgroup performance. In addition, we investigate group size as a moderator upon which this mediated relationship depends. We test these moderated‐mediated propositions using a split‐sample design and data from 248 military workgroups comprising 8,707 respondents. Findings from structural equation modeling reveal that diversity climate is consistently positively related to workgroup performance and that this relationship is mediated by discrimination. Results yield a pattern of moderated mediation, in that the indirect relationship between workgroup diversity climate (through perceptions of workgroup discrimination) and group performance was more pronounced in larger than in smaller workgroups. These results illustrate that discrimination and group size represent key factors in determining how a diversity climate is associated with group performance and, thus, have significant implications for research and practice. © 2014 Wiley Periodicals, Inc.